Microbial Metabolites in Multiple Sclerosis: Implications for Pathogenesis and Treatment - Duarte-Silva, Eduardo; Meuth, Sven G.; Peixoto, Christina Alves (Frontiers in Neuroscience, 2022)
Metabolites produced by the gut microbiota have been shown to play an important role in numerous inflammatory, neuropsychiatric, and neurodegenerative diseases. Specifically, microbial metabolites have been implicated in the modulation of innate and adaptive immunity, especially in the generation of regulatory T cells (Tregs), which are key regulators of multiple sclerosis (MS) pathogenesis. Furthermore, they affect processes relevant to MS pathophysiology, such as inflammation and demyelination, which makes them attractive molecules to be explored as therapeutics in MS. In this review, we discuss the importance of these metabolites as factors contributing to disease pathogenesis and as therapeutic targets in MS. Establishing an improved understanding of these gut-microbiota derived metabolites may provide new avenues for the treatment of MS.